Gender Differences in Modifying Lumbopelvic Motion during Hip Medial Rotation in People with Low Back Pain. (10th January 2012) - Hoffman, Shannon L.; Johnson, Molly B.; Zou, Dequan; Van Dillen, Linda R.
Abstract : Reducing increased or early lumbopelvic motion during trunk or limb movements may be an important component of low back pain treatment. The ability to reduce lumbopelvic motion may be influenced by gender. The purpose of the current study was to examine the effect of gender on the ability of people with low back pain to reduce lumbopelvic motion during hip medial rotation following physical therapy treatment. Lumbopelvic rotation and hip rotation before the start of lumbopelvic rotation were assessed pre- and posttreatment for 16 females and 15 males. Both men and women decreased lumbopelvic rotation and completed more hip rotation before the start of lumbopelvic rotation post-treatment compared to pre-treatment. Men demonstrated greater lumbopelvic rotation and completed less hip rotation before the start of lumbopelvic rotation than women both pre- and post-treatment. Both men and women reduced lumbopelvic motion relative to their starting values, but, overall, men still demonstrated greater and earlier lumbopelvic motion. These results may have important implications for understanding differences in the evaluation and treatment of men and women with low back pain.